Answer:
x = 3 - 3/2y
y = 2 - 2/3x
Step-by-step explanation:
2x + 3y = 6
2x = 6 - 3y
x = 3 - 3/2y
2x + 3y = 6
3y = 6 - 2x
y = 2 - 2/3x
Answer:
67.307
Step-by-step explanation:
30×25=750
100×80=8000
750+8000=8750
8750/130=67.307... total hits divided by total games
Answer:
(A) The population's growth rate in equation form is y = (0.016t * 7652) + 7652
(B) y = (0.016t * 7652) + 7652 =
y = (0.016(8) * 7652) + 7652 =
y = (0.128 * 7652) + 7652 =
y = 979.456 + 7652 =
y = 8631.456 (Or About) 8631
Step-by-step explanation:
(A) Y = the total population of the town. 0.016 is 1.6% just in its original form. T = the year in which were trying to find the town's total population. 7652 is the total population of the town in 2016. With this information, the equation reads, The total population of the town (Y) is equal to 16% (0.016) of the current year's population (T) added to 2016's population of 7652. (This last sentence can also be read what is 1.6% of the towns population in the year were trying to find. Because the population is always growing, 1.6% gets multiplied as to scale with the total population in year T)
(B) We just substitute (T) for 2024, or 8 years after 2016 (2024-2016) and simplify the equation we made.
Answer:
neither buy is better, both buys are $2.28571428/ounce
Based on the starting temperature and the new temperature, the relevant expression would be<u> 2 - (-9) </u>
To find the number of degrees the temperature has changed by, use the following equation:
<em>= Starting temperature - Current temperature </em>
Starting temperature = 2°F
Current temperature = -9°F
The equation becomes:
<em>= 2 - (-9)</em>
In conclusion, the expression would be 2 - (-9)
<em>Find out more on </em><em>expressions </em><em>at brainly.com/question/945593. </em>